Factors associated with dental fluorosis in children and teenagers from the city of Montería, Colombia - Espitia-Cabralez, Enalbis Esther; Lozano-Flórez, Milena Cecilia; Montoya-Vega, Martha Elena (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: dental fluorosis is the hypomineralization of enamel produced as a result of fluoride intake for a prolonged period during enamel formation. The aim of the present study was to identify the factors associated with dental fluorosis in children and teenagers from the city of Montería, Colombia. Methods: a quantitative, descriptive and retrospective study was conducted in a sample of 136 dental fluorosis cases in schoolchildren aged 6, 12, 15 and 18 years reported to the Surveillance and Control System from January to December 2016. Results: there was fluoride exposure in 81.6% of schoolchildren covered by the subsidized health system—the mechanism by which the poorest population, with not enough resources to pay, can access health services through a subsidy offered by the state in Colombia—. 89% were from the municipal center, defined by Colombia’s National Administrative Department of Statistics (Departamento Administrativo Nacional de Estadística, DANE) as the geographical area bounded by an urban perimeter, where the administrative headquarters of a municipality are located. 47% of patients had cavities. Tooth brushing in a frequency higher than three times a day was predominant with 48.5%, and the use of toothpaste on more than 3/4 of the brush with 52%. 71.3% of patients said they did not swallow toothpaste, and 93.4% did not swallow mouthwash. 82.4% of patients did not receive topical fluoride in the last year. Conclusions: several factors are more highly associated with dental fluorosis, such as the amount of toothpaste during brushing, the habit of brushing three or more times a day, consumption of diet salt, and unintentional intakeof toothpaste at an early age. Most schoolchildren had a moderate degree of dental fluorosis.